The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-44462009005000013
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da exposição à altitude sobre os aspectos neuropsicológicos: uma revisão da literatura

Abstract: ResumoObjetivo: Discutir os efeitos da exposição à altitude sobre as funções neuropsicológicas. Método: Foi realizada uma revisão de literatura usando como fonte de pesquisa artigos indexados no Pubmed, no período de 1921 a 2008, utilizando as palavras-chave "cognition and hypoxia", "hypoxia and neuropsychology", "acute hypoxia", "chronic hypoxia" e "acclimatization and hypoxia", além de livros específicos do assunto. Discussão: Os efeitos agudos e crônicos da hipóxia podem alterar inúmeras funções neuropsicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“… 35 It was reported that individuals living at high altitudes have severe sleep disorder, with the degree of change showing high correlations with altitude height and the duration of stay on a plateau area. 36 This phenomenon suggested that PSQI scores were significantly higher in the PDD group compared with the non-depressed PD group. Further logistic regression analysis found that sleep disorder was a risk factor for depression in PD patients.…”
Section: Discussionmentioning
confidence: 98%
“… 35 It was reported that individuals living at high altitudes have severe sleep disorder, with the degree of change showing high correlations with altitude height and the duration of stay on a plateau area. 36 This phenomenon suggested that PSQI scores were significantly higher in the PDD group compared with the non-depressed PD group. Further logistic regression analysis found that sleep disorder was a risk factor for depression in PD patients.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we believe that the worsening of sleep due to hypoxia impairs cognition. Other authors have stated that the effects of an altitude of 4,000 m can induce changes in mood, such as increased irritability and anger, and can worsen neuropsychological functions, such as attention, memory, and decision making (Bahrke & Shukitt-Hale, 1993;Lemos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, na condição de hipóxia, os voluntários apresentaram maiores escores de raiva, fadiga, confusão mental e DTH e diminuição do vigor de acordo com o instrumento BRUMS por um período de até 30 minutos após o cessamento do exercício, mesmo período em que os voluntários permaneceram em hipóxia. Tais resultados corroboram os achados de Lemos et al (2010) que observaram comportamento similar em indivíduos expostos a altitude durante 24 horas. Em contrapartida, um grupo de alpinistas que testaram estratégias de ascensão a grandes altitudes com o intuito de estabelecer uma melhor aclimatação não apresentaram diferenças significativas em tarefas que avaliaram o humor e a cognição (Bonnon, Noël-Jorand, & Therme, 1999).…”
Section: Discussionunclassified
“…Atualmente por diversas razões -incluindo o turismo, lazer, questões profissionais -o número de pessoas expostas a elevadas altitudes vem crescendo a cada ano (Sharma et al, 2014), assim como o número de estudos referente às alterações fisiológicas (Born et al, 2014) e do comportamento humano (Lemos et al, 2010) observadas em tal condição.…”
Section: Introductionunclassified